Job Satisfaction Analysis Through Supervision, Motivation And Organizational Culture - Martin (Journal of Social Science, 2020)
Main objective of this research is is to find out the effect of motivation and organizational culture to the job satisfaction are affecting both partially and simultaneously on Budisatrya Institution. Its research using cause and effect approach which measured the effect of independent variable to dependent variable. The population of its research are 97 the teachers of Budisatrya Institution as respondent. The data of the research are from questionnaire with Likert scale that were distributed and answered by the respondent. Double linear regression analysis is using of its research. The results show that all independent variable are positively and significantly affected to the job satisfaction. Supervision,motivation, and organizational culture are affecting job satisfaction,and dominant variable is supervision that Budisatrya do to their teachers. Keywords : Supervision, Motivation, Organizational Cultre, Jobs Sastisfaction.